Statistical tests for association - Morris, Andrew (Henry Stewart Talks, 2008)
Simple contingency table tests: genotypic test and Cochran-Armitage trend test, Logistic regression model for binary (case-control) data: incorporating covariates and extension to allow for multi-locus effects and interactions, Quantitative trait association analysis, Haplotype analysis: allowing for phase uncertainty in logistic regression model and methods for haplotype clustering, Software: statistical tests of association, genome-wide association analysis and haplotype analysis